2018
DOI: 10.1111/ddi.12787
|View full text |Cite
|
Sign up to set email alerts
|

Using Gradient Forests to summarize patterns in species turnover across large spatial scales and inform conservation planning

Abstract: AimProducing quantitative descriptions of large‐scale biodiversity patterns is challenging, particularly where biological sampling is sparse or inadequate. This issue is particularly problematic in marine environments, where sampling is both difficult and expensive, often resulting in patchy and/or uneven coverage. Here, we evaluate the ability of Gradient Forest (GF) modelling to describe broad‐scale marine biodiversity patterns, using a large dataset that also provided opportunity to investigate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…Some species with widely distributed recorded locations had poorer model fits than species with restricted ranges, perhaps reflecting the cosmopolitan distribution of the former (e.g., moderate explained deviance and AUC scores for killer whale and bottlenose dolphin) and the more aggregated nature of others for the latter (e.g., high explained deviance and AUC scores for Māui dolphin, Hector's dolphin). Evidence from previous studies have indicated that species with limited geographic ranges and/or environmental tolerances are generally better modelled than those with greater ranges (Morán‐Ordóñez, Lahoz‐Monfort, Elith, & Wintle, ; Stephenson et al, ; Thomson et al, ) because widespread species are less likely to have sharp easily identifiable environmental thresholds that clearly delineate their environmental niche (Morán‐Ordóñez et al, ). For species with limited ranges, the best model fits were commonly located closer to shore where sampling effort was highest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species with widely distributed recorded locations had poorer model fits than species with restricted ranges, perhaps reflecting the cosmopolitan distribution of the former (e.g., moderate explained deviance and AUC scores for killer whale and bottlenose dolphin) and the more aggregated nature of others for the latter (e.g., high explained deviance and AUC scores for Māui dolphin, Hector's dolphin). Evidence from previous studies have indicated that species with limited geographic ranges and/or environmental tolerances are generally better modelled than those with greater ranges (Morán‐Ordóñez, Lahoz‐Monfort, Elith, & Wintle, ; Stephenson et al, ; Thomson et al, ) because widespread species are less likely to have sharp easily identifiable environmental thresholds that clearly delineate their environmental niche (Morán‐Ordóñez et al, ). For species with limited ranges, the best model fits were commonly located closer to shore where sampling effort was highest.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reduced model fit could be influenced by historical events, human activities, population and species dynamics (e.g., migration, competition, predation, and for many cetacean species, social interactions; Elith & Leathwick, ) and temporal environmental patterns (e.g., diurnal, tidal, seasonal and annual patterns; fluctuating weather patterns; and prey distributions) which were not accounted for here. Despite these factors not being considered in a quantitative manner, model outputs are still valid for management purposes, but it should be noted that the representation of species' probability of occurrence are a smoothed representation of the raw data (spatially and temporally; Stephenson et al, ). Both RES and BRT analyses are correlative models and, in many cases, rely on biotic processes such as predation to be represented by environmental variables as proxies.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address some of these concerns, more recent approaches have combined continuous environmental data with biological samples (Dunstan et al 2012;Anderson et al 2016) with various statistical techniques used to quantitatively assess the role that different environmental factors play in influencing biodiversity patterns (Ferrier et al 2004;Pitcher et al 2012). Results can then be used to control the selection, weighting and transformation of environmental predictors, increasing the ability of the classification groups to represent spatial variation in biodiversity character (Leathwick et al 2011;Stephenson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One recently developed approach, Gradient Forests (GF, Pitcher et al (2011)) uses an aggregation of Random Forests (RF, (Breiman 2001)), each of which describes the environmental relationships of an individual species, to inform the selection, weighting and transformation of environmental predictors to maximise their correlation with species turnover (Ellis et al 2012). A GF-trained classification was recently used to describe spatial patterns of demersal fish species turnover (beta diversity) in New Zealand using an extensive demersal fish dataset (>27,000 research trawls) and high-resolution environmental data layers (1 km 2 grid resolution) (Stephenson et al 2018). Using a large set of independent data for evaluation, this classification was found to be highly effective at summarising spatial variation in both the composition of demersal fish assemblages and species turnover (Stephenson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation